Modelo contingencialista como preditor do grau de adaptação mercadológica de ofertas internacionais - Tafner, Rodrigo Esteves (2014)
This study aims to provide a predictive model of degree of adaptation required for the entry of a particular product in a particular target market, pointing to a position on a continuum of standardization / adaptation based on the contingency view particularly Jain, through the analysis of relationship indicators formed from secondary data and public access. To achieve this goal, a theoretical review pointed constructs not only Internationalization, but Organizational Psychology, and the Cultural Distance Hofstede, the gravitational theory proposed by authors such as Retail Reiley, Converse Huff and that should be integrated in a formative model predicting the degree of adaptation of the International Offering. The resulting theoretical model from the literature review was put to the test with data obtained from secondary databases as the Best Global Brands Ranking, GMID - Euromonitor and Global UN HDI and compared to data obtained using the Delphi method, in which 18 judges internationalization experts judged ex -post adjustment of 48 cases, 7 products in 6 countries over 1 item in only 6 of the 7 countries, by means of Partial Least Squares method - Structural Equation Modeling. The results point to a model with a high degree of prediction, with significance, after removing the bookmark Monetary Value of Brand originally proposed theoretical model. The final model, however can not be generalized because the study investigated some representative group of the population, but offers prospects for expansion of research is the expansion of the sample and the databases used either by the method of regression analysis in Multilevel function of the multi-stage characteristic of the sample.